Clinical Characteristics, Treatment Strategy, and Outcomes of Primary Large Cell Neuroendocrine Carcinoma of the Bladder: A Case Report and Systematic Review of the Literature - Xia, Kun; Zhong, Wenlong; Chen, Junyu; Lai, Yiming; Huang, Guohui; Liu, Hao; Dong, Wen; He, Wang; Lin, Tianxin; Huang, Jian (Frontiers in Oncology, 2020)
Purpose: The aim of this study was to review the clinicopathologic characteristics, treatments and outcomes of patients with primary large cell neuroendocrine carcinoma of the bladder (LCNEC). Patients and methods: We report one patient diagnosed with primary pure LCNEC of the bladder in Sun Yat-sen Memorial Hospital. In addition, we performed a systematic literature review, in April 2020, on case report and case series of LCNEC of the bladder. The clinicopathologic characteristics, treatments and outcomes of this rare disease were analyzed. Results: A total of 39 patients were included in our analysis (1 case from our institution and 38 cases from the literature). Most patients (79.5%) were male. The average age at the surgery for the patients is 61.5 years (range 19 – 85 years). The most common symptom was hematuria (n = 20, 76.9%). Almost all patients (38, 97.4%) underwent surgery, with 26 (66.7%) receiving multimodality therapy. Out of 24 patients with available data, regional or distant recurrences developed in 14 patients (58.3%). The median overall survival of the patients was 11.5 months, with 1- and 3-year survival rates of 54.0% and 21.4%, respectively. In the survival analysis, theT1-2 tumors (P = 0.025), no distant metastases at diagnosis (P = 0.001) and multimodality therapy (P = 0.017) were associated with better overall survival (OS). Conclusions: LCNEC of the bladder is an extremely rare neoplasm. The available data suggest that the disease has an aggressive natural history with poor prognosis. Early pathologic stage and multimodality treatment may be important factors in determining prognosis.